(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
One of the open problems in Physics is the analytical definition of time. This paper addresses a possible answer to this topic by proposing an analytical definition of time obtained by the Second Law of Thermodynamics and the Constructal Law approach.